2020
DOI: 10.1186/s41240-020-00174-7
|View full text |Cite
|
Sign up to set email alerts
|

Nutritive value and digestibility of macronutrients from sheep and alpaca skin hydrolysates as a new alternative in juvenile rainbow trout (Oncorhynchus mykiss) feeding

Abstract: Background The protein source from fish meal is very important in trout feeding, but it is expensive and very scarce. Alternative nutrient sources are required to achieve sustainability as trout production rapidly grows in Peru. The objective of this research was to determine the proximate chemical composition and the apparent digestibility coefficient (ADC) of dry matter, organic matter, crude protein, crude fat, and digestible energy of hydrolyzed sheep (HSS) and alpaca (HSA) skins in juvenile rainbow trout.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…In this context, León-López et al (2019) indicated that collagen is characterized by a high concentration of three major amino acids, glycine, proline, and hydroxyproline, which create its characteristic triple helix structure. Also, Araníbar-Araníbar et al (2020) indicated that the hydrolyzed sheep and alpaca skins have a high content of macronutrients with acceptable digestibility of the nutrients, making them a viable alternative to improve the nutritional value of rainbow trout rations. In addition, results of Iwai et al (2005) showed that the collagen is enzymatically hydrolyzed, and this breaks it down into smaller peptides (the primary complementary form of collagen) that are easily absorbed within the digestive tract before entering the circulation.…”
Section: Digestibility Coefficientmentioning
confidence: 99%
“…In this context, León-López et al (2019) indicated that collagen is characterized by a high concentration of three major amino acids, glycine, proline, and hydroxyproline, which create its characteristic triple helix structure. Also, Araníbar-Araníbar et al (2020) indicated that the hydrolyzed sheep and alpaca skins have a high content of macronutrients with acceptable digestibility of the nutrients, making them a viable alternative to improve the nutritional value of rainbow trout rations. In addition, results of Iwai et al (2005) showed that the collagen is enzymatically hydrolyzed, and this breaks it down into smaller peptides (the primary complementary form of collagen) that are easily absorbed within the digestive tract before entering the circulation.…”
Section: Digestibility Coefficientmentioning
confidence: 99%
“…Productive response of rainbow trout (Oncorhynchus mykiss) to the feeding regime with commercial feeds under intensive farming conditions in Lake Titicaca Marina Flores M. 1 , Rosario E. Ortega B. 2 , María del Pilar Blanco E. 3 , Marcelino J. Araníbar 4 *…”
mentioning
confidence: 99%